Meningkatkan Minat Wirausaha Siswa SMK untuk Mengurangi Kemiskinan dengan Perceived Desirability dan Feasibility - Asunka, Gallant; Widjajanta, Bambang; Lisnawati, Lisnawati (Universitas Pendidikan Indonesia, 2017)
The purpose of this study is how much influence is perceived desirability and feasibility on the interest of entrepreneurship in vocational students. The type of research used is descriptive, verification, with a total sample of 100 students. The data analysis technique used is multiple linear regression. The findings of the research on hypothesis testing can be seen that perceived desirability and feasibility have a positive / large category effect, both on the interest of entrepreneurship in vocational students. The originality of this research was found in the object of research, research period, measuring instruments and research results. The author also adds theories from foreign journals and foreign books.